Epitaxial growth of sexiphenyl on Al(111) from monolayer to crystalline films - Winter, Barbara (Langmuir : the ACS journal of surfaces and colloids, 2004)
A combination of in situ surface sensitive-techniques, UV photoemission and low energy electron diffraction, with ex situ bulk sensitive X-ray diffraction reveals the formation of epitaxial thin films of sexiphenyl on Al(111) starting from the first monolayer. For room temperature growth, highly ordered films are formed with a unique alignment of the sexiphenyl molecules with the long axes of all molecules aligned parallel to both the surface and the <10> azimuthal directions of Al(111). This is related to a densely packed highly commensurate first monolayer, which acts as a template for the unique (21) crystallite orientation observed